PENGARUH PROMOSI LIVE SELLING DAN HARGA PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK THE ORIGINOTE DI PLATFORM TIKTOK SHOP TAHUN 2023 - Aurora, Fajrin; Fretes, Mercy Devina De (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The Influence of Live Selling Promotions and Product Prices on Purchase Decisions for The Originote Products on the TikTok Shop Platform in 2023 This research aims to examine Live Selling Promotion and Product Prices on Purchase Decisions for The Originote products, using a quantitative approach. The research sample consisted of 100 respondents and was determined using the formula Hair et.al. using purposive sampling technique. The data processing technique used   is the   multiple linear regression method. The research results show that Live Selling Promotion and Product Prices, both partially and simultaneously, have a positive and significant effect on purchasing decisions for The Originote products, indicated by a significant value of 0.0000 < 0.05 and tcount > ttable (6.516 > 1.660 and 11.492 > 1.660) and the value of Fcount > Ftable (73,841 > 0.270). The results of the coefficient of determination test show that the Live Selling Promotion has an influence on the decision to purchase The Originote products by 48.7%, Product Price has an influence on the decision to purchase The Originote products by 67.9%. Simultaneously, these two independent variables influence the decision to purchase The Originote products by 69.7% and the remaining 30.3% is influenced by other variables not analyzed in this research.